Kombinasi Grey Relational Analysis (GRA) dan ROC Dalam Penentuan Promosi Jabatan Supervisor - Rio Andika (PT. Tech Cart Press, 2024)
Determining the promotion of supervisor position is a crucial process in managing human resources of an organization. This decision involves an in-depth evaluation of a supervisor's performance, leadership skills, ability to manage the team, as well as achievement of company goals and strategies. The benefits of this study provide recommendations to companies for determining supervisor promotion by applying a decision support system model using a combination of GRA and ROC so that it will help companies determine candidates who become supervisors. The calculation results recommend rank 1 with a total value of 0.9406 obtained on behalf of prospective candidates Ahmad and Astria, rank 2 with a total value of 0.8572 obtained on behalf of prospective candidate Joko, rank 3 with a total value of 0.7718 obtained on behalf of candidate Yudha, and rank 4 with a total value of 0.6974 obtained on behalf of prospective candidate Rina.